2008
DOI: 10.1200/jco.2007.12.5906
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations As an Independent Prognostic Factor in Patients With Advanced Colorectal Cancer Treated With Cetuximab

Abstract: These results confirm the high prognostic value of KRAS mutations on response to cetuximab and survival in metastatic CRC patients treated with cetuximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
776
2
27

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,346 publications
(835 citation statements)
references
References 22 publications
30
776
2
27
Order By: Relevance
“…Considering the molecular basis of EGFR-targeting agents, blocking EGFR at the receptor level will not ablate downstream signaling activities in tumors with KRAS mutations and hence constitutively active RAS proteins. Indeed, several studies have reported that KRAS mutations confer resistance to anti-EGFR monoclonal antibodies [24,48,[61][62][63][64][65]. KRAS mutations are associated with poor responses to therapy, reduced PFS and shorter OS in colorectal cancer patients treated with cetuximab alone or in combination with chemotherapy [48,[62][63][64][65].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the molecular basis of EGFR-targeting agents, blocking EGFR at the receptor level will not ablate downstream signaling activities in tumors with KRAS mutations and hence constitutively active RAS proteins. Indeed, several studies have reported that KRAS mutations confer resistance to anti-EGFR monoclonal antibodies [24,48,[61][62][63][64][65]. KRAS mutations are associated with poor responses to therapy, reduced PFS and shorter OS in colorectal cancer patients treated with cetuximab alone or in combination with chemotherapy [48,[62][63][64][65].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 99%
“…Indeed, several studies have reported that KRAS mutations confer resistance to anti-EGFR monoclonal antibodies [24,48,[61][62][63][64][65]. KRAS mutations are associated with poor responses to therapy, reduced PFS and shorter OS in colorectal cancer patients treated with cetuximab alone or in combination with chemotherapy [48,[62][63][64][65]. Similarly, an analysis of KRAS mutations in tumor samples from 92% of patients in a registrational clinical trial of panitumumab for the treatment of metastatic colorectal cancer predicted a lack of efficacy of panitumumab on PFS and OS in patients with KRAS mutant tumors [24].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Indeed, KRAS mutations result in constitutively active KRAS proteins that lead to continuous activation of the RAS signaling pathway independently of the upstream stimulation by EGFR ligands. As only patients with wild-type KRAS tumors benefit from therapies with anti-EGFR antibodies, accurate determination of the KRAS mutation status is crucial for ethical and economic reasons.…”
mentioning
confidence: 99%
“…Cetuximab (CTX), an anti‐EGFR monoclonal antibody, has been widely used particularly for treatment of colorectal and lung cancers 14, 15. However, some patients with colorectal cancer (CRC) are resistant to EGFR inhibitors because of the continuous activation of the RAS/mitogen‐activated protein kinase (MAPK) pathway by a mutation in codon 12 of the wild‐type v‐Ki‐ras2 Kirsten rat sarcoma viral oncogene homolog ( KRAS ) gene 14, 15, 16, 17. Therefore, the use of CTX is currently restricted to patients with wild‐type KRAS .…”
mentioning
confidence: 99%